Genetic analysis of grain yield and other traits of extraearly yellow maize inbreds and hybrid performance under contrasting environments - Badu-Apraku, Baffour; Oyekunle, M. (Elsevier, 2012)
Maize (Zea mays L.) is a major staple crop in West and Central Africa (WCA) but production is constrained by Striga hermonthica parasitism and recurrent drought in the savannas where maize yield potential is highest due to low night temperatures, high solar radiation and low incidence of diseases. Two studies were conducted for 2 yr at 5 locations in Nigeria to determine the combining ability of seven extra-early yellow-grained inbreds, place them into heterotic groups, identify the best testers and superior single-cross hybrids when Striga-infested, and under drought stress at flowering and grain filling, in optimal conditions and across environments. General combining ability (GCA) and specific combining ability (SCA) mean squares were significant for grain yield and most other traits across research environments. Mean squares for GCA were larger than those of SCA in all environments, indicating that additive gene action is more important in the inheritance of traits. Three testers (TZEEI 79, TZEEI 76 and TZEEI 63) and opposing heterotic groups (TZEEI 95, TZEEI 78, TZEEI 79), (TZEEI76, TZEEI 82) and TZEEI 63, TZEEI 58) were identified across environments. TZEEI 79 had the highest positive GCA effects across environments. Furthermore, TZEEI 95 x TZEEI 78, TZEEI 95 x TZEEI 79, TZEEI 78 x TZEEI 79 were identified as the potential single-cross testers for the development of three-way and double-cross hybrids. Results of repeatability analysis showed that the managed drought test site, IKDT, was the most repeatable even though it was not very discriminating. In contrast, the high yield, optimal growing test site, ZAWW, had high representativeness, discriminating ability and repeatability, indicating that it is the ideal test location. The best extra-early hybrid TZEEI 79 x TZEEI 63 under drought stress and TZEEI 82 x TZEEI 79 under Striga infestation, out-yielded the best open-pollinated early check by 3% and 12%, respectively. TZEEI 79 x TZEEI 76 was the highest yielding and most stable hybrid across environments. The available extra-early maize inbred lines are not only drought escaping but also possess genes for drought tolerance.